Identity of foreign language pre-service teachers to speakers of other languages: insights from Brazil and Chile - Archanjo, Renata; Barahona, Malba; Finardi, Kyria Rebeca (Colombian Applied Linguistics Journal, 2019)
The aim of this paper is to examine the identity of foreign language (FL) pre-service teachers in two distinct contexts: Brazil and Chile. A multiple case study methodology was used to investigate how foreign language pre-service teachers develop and conceptualize their teacher identity in three different teacher education programs—two in Brazil and one in Chile. The analysis focused on three main issues: emerging identities, the role of foreign language proficiency, and the practicum as a mediating space to develop teacher identity. Results of the two case studies situated in Brazil suggest that FL pre-service teacher identity is shaped by their beliefs on language proficiency. The case study in Chile confirmed that pre-service teachers’ identity oscillates between identifying as students and as teachers. Overall, results of the study suggest that FL teacher identity is shaped by notions of legitimization of the teacher’s role and language proficiency.